Squaring the circle? Integrating environment, infrastructure and risk reduction in Post Disaster Needs Assessments. (December 2018) - Hinzpeter, Kilian; Sandholz, Simone
Abstract: Disasters triggered by natural hazards such as floods, droughts or cyclones have the potential to cause large-scale damage on regional, national or even supranational scale. To cope with the impacts and to facilitate reconstruction the Post Disaster Needs Assessment (PDNA) tool was developed. Its main goal is to assess damages and resulting early and long-term recovery needs and priorities. The assessment, a government-led exercise with support from the United Nations, the European Commission, the World Bank and others, is divided into different sectors, including environment, disaster risk reduction, and infrastructure as key topics. However, in reality the potential of this integrated approach is far from being fully exploited. The relevance of sound environmental conditions for recovery are under addressed in the other sector reports, such as the consideration of ecosystem-based approaches for disaster risk reduction and as part of green or hybrid infrastructures. Based on an in-depth assessment of past PDNA reports and a qualitative empirical survey among experts involved in these studies, this paper aims at assessing underlying reasons for the negligence of environmental aspects and potentials against other needs. After comparing the described environmental damages against proposed recovery strategies in the respective sector – if made at all – we highlight related potential shortcomings and challenges. In a second step, the proposed (engineered) risk reduction measures are analyzed regarding their consideration of ecosystem-based approaches. We conclude by proposing potentials to leverage environmental considerations and ecosystem-based solutions into risk reduction strategies.